MODEL ANALISIS JALUR PADA LOYALITAS USER ATAS KUALITAS PELAYANAN DAN KINERJA KARYAWAN MELALUI MEDIASI KEPUASAN USER PADA PT BINTANG KARYA SARANA JAKARTA - Prabowo, Soekardi Hadi; Hardyaningwati, - (E-journal Widya Eksakta, 2020)
In the labor supply business, user satisfaction is greatly influenced by the quality of service provided by outsourced employees as an interaction with consumers. In addition to service quality, employee performance also plays a very important role in influencing user satisfaction, because through company employees interact with users. This study aims to identify and analyze the effects of: employee performance on service quality, employee performance on user satisfaction, quality on user satisfaction, employee performance on user loyalty, service quality on user loyalty and user satisfaction on user loyalty. The method used is path analysis. The test results show that: 1) employee performance has an effect on service quality. 2) employee performance affects user satisfaction. 3) service quality affects user satisfaction. 4) employee performance does not have a direct effect on user loyalty, but employee performance has an indirect effect by passing satisfaction as an intervening variable then influencing their loyalty. 5) service quality has no direct effect on user loyalty, but service quality has an indirect effect by passing satisfaction as an intervening variable then influencing their loyalty. 6) User satisfaction affects user loyalty.